PENGARUH PRICE EARNING RATIO, DEBT TO EQUITY RATIO DAN DIVIDEND PAYOUT RATIO TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR BASIC MATERIALS YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2017-2020 - Wildan Diky Fathoni; Zaenul Muttaqien; Suseno Hendratmoko (Jurnal Bisnis Islam dan Kewirausahaan, 2023)
This study aims to analyze the Price Earning Ratio (PER), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR) on Firm Value in the Basic Material company sector listed on the Indonesia Stock Exchange for the 2017-2020 period. Price Earning Ratio (PER) is a ratio commonly used by investors to analyze whether the company is good or not in the future. The type of data used is using secondary data in the form of financial reports of Basic Material sector companies listed on the Indonesian stock exchange for the 2017-2020 period. The population and samples in this study amounted to 8 companies with the 2017-2020 time period with 32 financial reports obtained. The analysis technique used in this study uses Panel Data Regression Technique. Based on the results of the analysis conducted, the results obtained Price Earning Ratio (PER) has a significant effect on firm value. Debt to Equity Ratio (DER) has no significant effect on firm value. Dividend Payout Ratio (DPR) has a significant effect on company value. The results of the analysis simultaneously Price Earning Ratio (PER), Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR) affect the value of the company. Keywords: Price Earning Ratio (PER), Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR) and Company Value.